Problems of translation of Orthodox non-equivalent lexis to English - Knežević, Ivana; Zoran, Ranković (KAMASEAN: Jurnal Teologi Kristen, 2024)
Cultural elements and systems often do not match up between two cultures which use different languages, which represents one of the main problems in the domain of translation. This paper is focused on the problems in translating non-equivalent lexicon specific to the Eastern Orthodox Church. The paper presents an overview and a detailed explanation of translation procedures used in dealing with this issue. The author begins with the non-equivalent words in Serbian, as the source language, since it is the language of the community which has been for many centuries back predominantly Eastern Orthodox and thus possesses an appropriate language “apparatus”, and observes their translation equivalents in English, as the target language. The research will show that the choice of the translation procedures is often not exclusively a matter of language. The good translator must not only have a good knowledge of the target language, but also must be familiar with the specific features of the religion and culture of the given society and the source language. Besides, we will point out that the target audience is also an important factor that must be observed in the process of translation.